Process route selection for inherently safer design based on consequences analysis - Mardhati, Zainal Abidin; Mohd Sobri, Takriff, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/